Development of Web-Based Educational Cards for the IPAS Subject in Grade 5 of Elementary School - Fivi Aledia; Mahmud Alpusari (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study aims to develop web-based card education with the theme of a harmonious ecosystem for IPAS content in grade 5 elementary school. This study aims to test the feasibility and practicality of web-based card education with the theme of a harmonious ecosystem used by grade 5 students at SDN 012 Kuantan Sako in September. This research is a Research and Development (R&D) study using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The results of the expert validation obtained an overall average of 91.67% in the very feasible category. The overall average score of the student response questionnaire was 92.083% in the very practical category. The overall average score of the teacher response questionnaire was 93.75%, categorized as highly practical. Based on these data, web-based card education with a harmonious ecosystem theme is highly feasible and practical for use in science learning in grade 5 elementary school.